Cadmium stress alters heterophylly, anatomy, and photosynthetic activity of Hygrophila difformis - Abeer Kazmi; Gaojie Li; Jingjing Yang; Xuyao Zhao; Md. Fakhrul Islam; Xiaozhe Li; Seisuke Kimura; Hongwei Hou (Ecotoxicology and Environmental Safety)
Cadmium (Cd) is a toxic metal that poses an environmental risk, but its effects on amphibious plants like Hygrophila difformis, which thrive in both terrestrial and submerged conditions, remain unexplored. This study investigates the morphological, anatomical, and physiological responses of H. difformis to Cd exposure. H. difformis was exposed to 0, 1, 2, and 4 mg/L Cd for 30 days under both terrestrial and submerged conditions. Leaves were examined at 10, 20, and 30 days for morphological and physiological changes. At lower Cd concentration (1 mg/L), leaf morphology showed minimal changes compared to the control. Submerged control leaves were highly dissected (26.1 ± 0.45), whereas dissection was substantially reduced at 4 mg/L Cd (16.96 ± 0.67), indicating a profound impact on heterophylly. Cd stress affected leaf size significantly, particularly in submerged plants (17.8 ± 3.22 cm²) compared to controls (39.2 ± 2.84 cm²). Furthermore, compared to terrestrial leaves (4.27 ± 0.31 mg/kg), submerged leaves accumulated significantly higher content of Cd (45.2 ± 6.66 mg/kg), indicating higher absorption under aquatic conditions. Terrestrial leaves appeared more resistant; however, higher concentrations caused tissue damage. Following 30 days of treatment, qualitative TEM-based anatomical analysis revealed noticeable cell shrinkage and fewer visible chloroplasts in submerged leaves compared to controls, while terrestrial leaves exhibited thicker cell walls. Cd exposure also inhibited photosynthesis, reducing pigment levels and enzyme activity. Interestingly, Rubisco activity increased in submerged leaves after 30 days of high Cd exposure, preventing the transition from C3 to C4 photosynthesis. H. difformis exhibits poor growth under Cd stress and can serve as a bioindicator for heavy metal pollution.